The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1021/jm00055a011
|View full text |Cite
|
Sign up to set email alerts
|

Substituted 3-(phenylmethyl)-1H-indole-5-carboxamides and 1-(phenylmethyl)indole-6-carboxamides as potent, selective, orally active antagonists of the peptidoleukotrienes

Abstract: Substituted indole-5-carboxamides and indole-6-carboxamides have been found to be potent and selective antagonists of the peptidoleukotrienes. Initial derivatives of these series (4-[[5-[(cyclopentylmethyl)carbamoyl]-1-methylindol-3-yl] methyl]-3-methoxy-N-[(2-methylphenyl)sulfonyl]benzamide (5a) and 4-[[6-[(cyclopentylmethyl)carbamoyl]-3-methylindol-1-yl] methyl]-3-methoxy-N-[(2-methylphenyl)sulfonyl]benzamide (6a), respectively), when compared to the corresponding indole amides (e.g. 28 and 29), were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In addition, various carboxamide and sulfonamide derivatives exhibited a pattern of no effect or partial agonist effects in vivo despite good binding affinity (Singer et al, 1998). These latter derivatives also showed potent antagonist activity for the peptidoleukotrienes, a class of eicosanoids (Jacobs et al, 1993; Matassa et al, 1990). …”
Section: 0 Discussionmentioning
confidence: 99%
“…In addition, various carboxamide and sulfonamide derivatives exhibited a pattern of no effect or partial agonist effects in vivo despite good binding affinity (Singer et al, 1998). These latter derivatives also showed potent antagonist activity for the peptidoleukotrienes, a class of eicosanoids (Jacobs et al, 1993; Matassa et al, 1990). …”
Section: 0 Discussionmentioning
confidence: 99%
“…Based on the above reports, we explored the synthesis of new indole propanamide derivatives 5(a-e) to be potent antibacterial and antifungal agents when tested against precarious pathogenic microorganisms such as Pseudomonas aureginosa, Escherichia coli, Vibrio cholerae, Staphylococcus aureus and antifungal activity against Candida albicans, Aspergillus niger, Penicillin chrysogenum and Cladosporium oxysporum. The rationality in investigating the biopotency of indole-3-propanamide derivatives is due to its use as precursors to obtain several biologically active molecules, especially for the treatment of brain disorder [6], as tyrosine kinase inhibitors, inhibitors of epidermal growth factor (EGF) receptor [7], immunosuppressive activity [8] anti-allergic [9] and inflammation inhibitors [10]. Thus, indole-3-propanamides have become an important precursor for various pharmaceutically important compounds [11][12][13], and there is flexibility in exploring indole-3propanamide derivatives randomly for various biological activities to get suitable hits.…”
Section: Introductionmentioning
confidence: 99%
“…20 Although the corresponding indolylalkylamides exhibited only moderate anti-edematous effect, to our surprise, results of pharmacological screening tests revealed that some of these compounds significantly inhibited IL-4, IL-5 biosynthesis and/or histamine release. These data and the fact that indole constitutes the central core of numerous potent LTD 4 antagonists, [21][22][23] PAF antagonists, 24 or inhibitors of FLAP, 12 prompted us to carry out an extensive pharmacomodulation in this series. We report here the results of in vitro and in vivo investigations in the N-(pyridin-4-yl)-(indol-3-yl)alkylamides 44-84 (Table 3).…”
Section: Introductionmentioning
confidence: 99%